Adsorption of Low-Phosphate in Water Using Commercial Fe-based Adsorbents - Faris, Salman; Nurhayati, Ervin (Dampak, 2025)
Phosphate contamination in aquatic environments has become a serious issue due to its role in eutrophication, leading to excessive algal growth and degraded ecosystems. Anthropogenic activities such as agricultural runoff and wastewater discharge significantly increase phosphate concentrations. Among treatment technologies, adsorption using iron-based adsorbents has shown high efficiency, especially at low concentrations. However, performance is influenced by adsorbent type, particle size, and hydrodynamic conditions. This study evaluated the phosphate adsorption performance of Granular Ferric Hydroxide (GFH) and Bayoxide E33 with particle sizes of 74–149 µm, 37–74 µm, and <37 µm. Batch experiments were conducted with 0.3 mg P/L phosphate solution. The isotherm study was performed over 180 minutes, and the kinetics study extended to 240 minutes. Surface morphology was characterized by SEM, and specific surface area was analyzed using BET, which confirmed that smaller particles exhibited higher surface areas. Results showed that GFH <37 µm achieved the highest adsorption capacity of 7.5 mg/g, while Bayoxide <37 µm reached 6.18 mg/g. The Langmuir model best described the isotherm data, and the Pseudo Second-Order model indicated chemisorption as the dominant mechanism. These findings underscore the importance of optimizing particle size to enhance phosphate removal. Keyword: Adsorption, Bayoxide, GFH, Particle Size, Phosphate